2015
DOI: 10.1179/1743294415y.0000000018
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of corrosion protection by cold spray coatings

Abstract: Cold spray is a high deposition rate coating process, in which solid powder particles are accelerated to velocities ranging between 300 and 1200 m s − 1 through a de Laval nozzle, impact and adhere to a substrate or previously deposited coating. The powder feedstock remains well below its melting temperature during deposition. Therefore, cold spray is categorised among solid state deposition methods, and offer significant advantages as compared to other traditional thermal spray techniques.Particles/substrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(55 citation statements)
references
References 78 publications
0
52
0
Order By: Relevance
“…The fine powders, with narrow size distribution and containing low oxygen content are usually more suitable and desirable 90 . Also, the plastic deformation can occur more easily depending on the crystalline structure 1, 40,52,90 .…”
Section: Some Relevant Corrosion Studies Of Cold Spray Coatings and Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The fine powders, with narrow size distribution and containing low oxygen content are usually more suitable and desirable 90 . Also, the plastic deformation can occur more easily depending on the crystalline structure 1, 40,52,90 .…”
Section: Some Relevant Corrosion Studies Of Cold Spray Coatings and Cmentioning
confidence: 99%
“…The fine powders, with narrow size distribution and containing low oxygen content are usually more suitable and desirable 90 . Also, the plastic deformation can occur more easily depending on the crystalline structure 1, 40,52,90 . All these effects on the coating formation are described in literature 1, 42 and some studies show that they have high influence in the corrosion protection performance 62 .…”
Section: Some Relevant Corrosion Studies Of Cold Spray Coatings and Cmentioning
confidence: 99%
“…Studies reported that the fatigue and corrosion properties of Mg alloys can be improved by surface modification in CS method [12][13][14][15][16][17][18] by employing different coating materials, which has higher strength and better corrosion resistance. Aluminum and its alloys (AA) have shown to be an excellent coating material for coating the surface of the Mg alloy parts [19]. When AA comes in contact with air a thin aluminum oxide layer is made which protects the substrate from penetration of the oxygen which in turn results better oxidation resistance.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, this increases the range of methods used for superhydrophobic coatings production.Superhydrophobic surfaces (SHS) are actively studied across a wide range of applications and industries. As a rule, with the unique water-repelling feature of these surfaces, their use is associated with the ability to reduce wear of metal surfaces due to corrosion in the aquatic environment [16][17][18][19]. Superhydrophobic surfaces can minimize the interaction between metal substrates and corrosive substances and provide better anti-corrosion properties by reduction of contact time with water [16][17][18]20,21].…”
mentioning
confidence: 99%
“…As a rule, with the unique water-repelling feature of these surfaces, their use is associated with the ability to reduce wear of metal surfaces due to corrosion in the aquatic environment [16][17][18][19]. Superhydrophobic surfaces can minimize the interaction between metal substrates and corrosive substances and provide better anti-corrosion properties by reduction of contact time with water [16][17][18]20,21]. Often it facilitates self-cleaning potential taking advantage of low water adhesion [16,18,19,[22][23][24].…”
mentioning
confidence: 99%